The Second Language Acqusition The Fifth Grade Student of SDN Ujungaris 1 Indramayu - Dede Irawan (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2019)
This research is aimed to know how do the students get second language acquisition and this research used qualitative descriptive method to analysis second language acquisition in the student. The result shows there were 15 people from 20 students who get a second language through receptive, In this process the students need at least 2 meetings in the teaching process to mastery second language acquisition although in one semester they only can mention vocabulary. Whereas there are 5 students who can speak several words and begin to form short phrases, although grammatically is not correct, this stage is called the early production process of second language acquisition. Besides that, the second language acquisition of students is not only obtained from English language teaching but also other factors that influence it, the result shows there were 5 students who get second language acquisition from YouTube social media and three of them take English language coursesPenelitian ini bertujuan untuk mengetahui bagaimana cara siswa memperoleh penguasaan bahasa kedua dan penelitian ini penulis menggunakan metode kualitatif untuk menganalisis penguasaan bahasa kedua pada siswa. Hasilnya menunjukkan ada 15 orang dari 20 siswa yang mendapatkan bahasa kedua melalui penerimaan, Dalam proses ini para siswa membutuhkan setidaknya 2 pertemuan dalam proses pengajaran untuk menguasai penguasaan bahasa kedua meskipun dalam satu semester mereka hanya bisa menyebutkan kosa kata. Sedangkan ada 5 siswa yang dapat berbicara beberapa kata dan mulai membentuk frasa pendek, meskipun secara tata bahasa tidak benar, tahap ini disebut proses produksi awal penguasaan bahasa kedua. Selain itu, akuisisi bahasa kedua siswa tidak hanya diperoleh dari pengajaran bahasa Inggris tetapi juga faktor-faktor lain yang mempengaruhinya, hasilnya menunjukkan ada 5 siswa yang mendapatkan akuisisi bahasa kedua dari media sosial YouTube dan tiga dari mereka mengambil kursus bahasa Inggris. Keyword : Second Language Acquisition and Student